Complementary Approaches to Systematic Ichthyology - Hastings, Philip A. (Zootaxa, 2011)
The molecular revolution in phylogenetic biology and its widespread application to fishes has in some ways complicated the task of teaching my craft of ichthyology. Beginning students know nothing of the history of fish classifications, how they were created, how they have changed over the years or how and why they continue to change. On the first day of class I typically bring in the four editions of Joe Nelson’s classic Fishes of the World (Nelson, 1976, 1984, 1994, 2006) to show students that systematic ichthyology is a vibrant and dynamic science and that these are exciting times. Then I add that the latest of these encyclopedias of our current knowledge has for the most part not incorporated the more radical changes in our understanding of fish relationships suggested by many recent analyses of molecular data. It is not difficult to imagine students’ frustration when one moment I tell them that the Scorpaeniformes is a long-recognized lineage of fishes, show them the distinctive morphological features shared by the group, then go on to say that the group is likely not monophyletic and that the character homologies upon which traditional diagnoses of the group were based are homoplasious (Imamura & Shinohara, 1997, 1998; Smith & Wheeler, 2004; Shinohara & Imamura, 2007). That realization may be exciting to some but must be nothing short of maddening to a novice. But in time, if my students and I do our jobs well, they too will learn to relish the vibrant science that systematic ichthyology continues to be.